Syntax and the failure of analogical generalization: A commentary on Ambridge (2020). Issue 5 (October 2020) - Adger, David
The syntactic behaviour of human beings cannot be explained by analogical generalization on the basis of concrete exemplars: analogies in surface form are insufficient to account for human grammatical knowledge, because they fail to hold in situations where they should, and fail to extend in situations where they need to.